Association of G6PD with lower haemoglobin concentration but not increased haemolysis in patients with sickle cell anaemia - Nouraie, Mehdi; Reading, Noel S; Campbell, Andrew; Minniti, Caterina P; Rana, Sohail R; Luchtman-Jones, Lori; Kato, Gregory J; Gladwin, Mark T; Castro, Oswaldo L; Prchal, Josef T; Gordeuk, Victor R (British journal of haematology, 2010)
The genetic bases of the highly variable degrees of anaemia and haemolysis in persons with Hb SS are not fully known, but several studies have indicated that G6PD deficiency is not a factor. The G6PD(202A) and G6PD(376G) alleles and alpha-thalassaemia were determined by molecular genetic testing in 261 children and adolescents with Hb SS in a multicentre study. G6PD(202A,376G) (G6PD A-) was defined as hemizygosity for both alleles in males and homozygosity in females. Among the participants 41% were receiving hydroxycarbamide. The prevalence of G6PD(202A,376G) was 13.6% in males and 3.3% in females with an overall prevalence of 8.7%. G6PD(202A,376G) was associated with a 10 g/l decrease in haemoglobin concentration (P = 0.008) but not with increased haemolysis as measured by lactate dehydrogenase, bilirubin, aspartate-aminotransferase, reticulocyte count or a haemolytic component derived from these markers (P > 0.09). Similar results were found within a sub-group of children who were not receiving hydroxycarbamide. By comparison, single and double alpha-globin deletions were associated with progressively higher haemoglobin concentrations (P = 0.005 for trend), progressively lower values for haemolytic component (P = 0.007), and increased severe pain episodes (P < 0.001). In conclusion, G6PD(202A,376G) may be associated with lower haemoglobin concentration in sickle cell anaemia by a mechanism other than increased haemolysis.